Method for preparing insole by adopting polyurethane foaming particles and insole prepared by method

By treating graphene oxide on the surface of the TPU sole and combining porous mold technology, the contradiction between breathability and wear resistance of the existing TPU sole is solved, and the breathability, wear resistance and odor removal effect is improved, and the sole is maintained. Elasticity and visual effects.

CN119283269APending Publication Date: 2025-01-10MAOTAI FUJIAN SOLES CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411535325.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing TPU soles damage wear resistance and elasticity when pursuing breathability, and the manufacturing of breathable holes will affect the strength of the sole structure, resulting in a reduced comfort.

Method used

Polyurethane foamed particles with graphene oxide on the surface are used to form breathable channels through high temperature treatment, and a porous mold is used to achieve integrated molding visual effect, increasing the density of the surface breathable pores to improve wear resistance and odor removal effect.

Benefits of technology

It achieves good breathability and wear resistance, maintains the elasticity of the popcorn sole, and improves the odor removal effect and wear resistance of the visual part, and can set complex patterns on the sides without being affected by popcorn patterns.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119283269A_ABST
    Figure CN119283269A_ABST
Patent Text Reader

Abstract

The invention relates to a method for preparing a midsole by using polyurethane foaming particles and the midsole prepared thereby, and the method comprises the following steps: mutually fusing the foaming particles with graphene oxide on the surface in a midsole mold under the condition of heating by using water vapor to form the thermoplastic midsole, wherein the body of the foamed particle with the graphene oxide on the surface is formed by mixing 60 wt% to 98 wt% of thermoplastic polyurethane and 2 wt% to 40 wt% of thermoplastic polymer and foaming under a non-curing condition. The thermoplastic insole disclosed by the invention is high in mechanical strength, good in thermal stability, good in chemical erosion resistance and good in air permeability, and is suitable for outdoor and extreme environments; the graphene oxide on the surface of the foamed particles enables the foamed particles in the place with graphene not to be fused with other foamed particles, so that a ventilation channel is naturally left; the breathable channels improve the breathability of the shoes and improve the wearing comfort.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sole manufacturing, in particular to a method for preparing a midsole by using polyurethane foam particles and the prepared midsole. Background Art

[0002] The appearance of the popcorn sole is formed by thousands of "popcorns" arranged closely together. The full name of this sole material is polyurethane thermoplastic elastomer, also known as ETPU sole. Its production principle is to increase the volume of the original 0.5mm particle by about 10 times by subjecting each TPU particle to high temperature and pressure, forming elliptical non-cross-linked foamed particles ETPU containing micro-closed bubbles, which are named after their "popcorn" shape. These elliptical non-cross-linked foamed particles with micro-closed bubbles are closely arranged, forming the unique appearance and structure of the popcorn sole.

[0003] Supercritical foaming technology has been widely used in shoe materials. This process has gradually become a "black technology" force in the field of shoe materials and has been slowly introduced to the market. TPU shoe materials using supercritical foaming technology have become one of the most high-end shoe materials. However, although TPU soles have good wear resistance and elasticity, their air permeability is relatively poor, which may cause dampness, stuffiness, stinky feet, and even athlete's foot.

[0004] Various soles with air holes are designed in the prior art, but the soles will also damage the strength of the soles to a certain extent, and the wearer's soles may feel the air holes of the soles, thereby affecting the comfort of wearing. Moreover, in the manufacturing process of TPU soles, air holes can generally only be prefabricated during the molding process, and it is best not to make air holes after the soles are molded, because the manufacture of these air holes will damage the structure of the popcorn unit and affect the strength of the popcorn around the air holes, because the epidermis of the popcorn unit usually has the highest strength, and the bubbles inside are protected by the epidermis, and when the epidermis is damaged, the strength around the air holes will deteriorate.

[0005] There is no technology in the prior art that is both breathable and can maintain the good wear resistance and elasticity of the existing TPU shoe materials.

[0006] In view of this, the inventor conducted in-depth research on the above-mentioned issues, and thus the present invention was produced. Summary of the invention

[0007] The present invention provides a method for preparing a midsole by using polyurethane foam particles, a midsole prepared therefrom, and a midsole prepared therefrom, so as to overcome the shortcomings of the above-mentioned sole preparation. The prepared midsole has good air permeability while still retaining the good wear resistance and elasticity of the popcorn midsole shoe material in the prior art.

[0008] The present invention adopts the following technical solution: A method for preparing a midsole using polyurethane foam particles and the midsole prepared therefrom, comprising the following steps: 1) Preparation of foamed particles having graphene oxide on the surface, as follows: Method S1, contacting a graphene oxide suspension with the polyurethane foam particles, wherein the graphene oxide suspension further contains a binder, to obtain polyurethane foam particles having graphene oxide on the surface; Alternatively, method S2, fully mix the polyurethane matrix in a molten state with a foaming agent in a supercritical state (such as carbon dioxide or nitrogen or other gases) to form a single-phase mixed sol; The single-phase mixed sol is passed through an extrusion die and enters a normal pressure state, so that a large number of bubble nuclei are precipitated from the foaming agent and expand to obtain hot polyurethane foam particles; Mixing powdered graphene oxide with the hot polyurethane foam particles, and cooling the mixture to form the polyurethane foam particles having graphene oxide on the surface; 2) placing the foamed particles in the mold, and introducing steam at a first temperature into the mold, wherein the first temperature is between the softening point of the foamed particles and a temperature 18° C. higher than the softening point, and the treatment time is 1 minute to 20 minutes, so that the foamed particles undergo secondary foaming and are mutually welded to form a midsole precursor; 3) maintaining one or more of the above molds in an atmosphere of a second temperature, wherein the second temperature is 20°C to 30°C higher than the first temperature, and the treatment time is 1 minute to 20 minutes, so that an integrated molding visual effect is formed in the integrated molding visual area of ​​the above midsole precursor to form the above midsole.

[0009] Furthermore, the amount of the graphene oxide is 0.02wt%-2wt% of the polyurethane foam particles.

[0010] Furthermore, the graphene oxide is sulfonated graphene, the flake diameter of the sulfonated graphene is 100 micrometers to 1000 micrometers, the thickness of each sulfonated graphene is 5nm to 10nm, and the flake diameter uniformity and thickness uniformity of the sulfonated graphene are both greater than 90%.

[0011] Furthermore, the above-mentioned mold is a porous mold, which is provided with a plurality of first air holes corresponding to the visual part of the above-mentioned integrally formed visual area, wherein the area of ​​each of the above-mentioned first air holes is 0.01 square millimeters to 0.25 square millimeters, and the number of the above-mentioned first air holes is greater than 50 per square centimeter.

[0012] Furthermore, the above-mentioned foamed particles include 60wt% to 98wt% of foamed particles made of polyurethane and 2wt% to 40wt% of foamed particles made of other materials, wherein the polyurethane is one or more of polyester polyurethane, polyether polyurethane and aliphatic polyurethane, and the other materials are one or more of polyether nylon elastomer (PEBAX), polyester elastomer (TPEE) and ethylene vinyl acetate polymer (EVA).

[0013] A plurality of second air holes are provided in the non-visual part of the mold that does not correspond to the one-piece visual area, and the area of ​​each of the second air holes is greater than 0.3 square millimeters and less than 3 square millimeters, and the number of the second air holes is less than 10 per square centimeter, for example, 0.5 to 3 per square centimeter.

[0014] The polyurethane is an aliphatic polyurethane, which is prepared by reacting a liquid composition. The liquid composition includes a polyurethane generating component and a reaction catalyst, wherein the polyurethane generating component includes an isocyanate component A and an isocyanate reactive component B, and the isocyanate component A includes an aliphatic diisocyanate and / or an aliphatic polyisocyanate; the aliphatic isocyanate includes hexamethylene diisocyanate, cyclohexylene diisocyanate, isophorone diisocyanate, etc.

[0015] The polyurethane made from the composition has a hydrocarbon skeleton of polyvinyl alcohol and good biocompatibility. The polyurethane foam material has at least one of the effects of temperature resistance, good thermoplasticity, and stable shrinkage rate of molds.

[0016] The isocyanate component B comprises: B1) one or more organic polyols with a functionality of 2-3; B2) low molecular weight polyvinyl alcohol, wherein the molecular weight of the low molecular weight polyvinyl alcohol is 300 to 10000, wherein the initial viscosity of the liquid composition at 25°C is 50-5000 mPa.s (measured according to DIN EN 53019), and the ratio of the number of NCO groups in the isocyanate component A to the number of OH groups in the isocyanate component B is 1.05:1 – 1.1:1.

[0017] The polyurethane prepared from the composition has a hydrocarbon skeleton of polyvinyl alcohol and has good biocompatibility. The one or more organic polyols include one or more selected from the following: pentaerythritol, ethylene glycol (EG), 1,2-propylene glycol, 1,4-butylene glycol, 1,6-hexanediol, neopentyl glycol (NPG), diethylene glycol (EG), dipropylene glycol, trimethylolpropane (TMP), glycerol, diethylene glycol, methylpropylene glycol, polyether polyol, polyether carbonate polyol, polyester polyol, polycarbonate glycol or polyol based on vegetable oil.

[0018] A shoe comprises a midsole made by the method for making a midsole using foamed particles.

[0019] From the above description of the structure of the present invention, it can be seen that compared with the prior art, the present invention has the following advantages: 1. In the method of the present application, during the high-temperature fusion process of the graphene oxide on the surface of the polyurethane foam particles, the graphene oxide itself also forms a stable chemical bond with the hydroxyl or isocyanate groups on the surface of the polyurethane foam particles. The graphene has a multi-layer structure so that the polyurethane foam particles where the graphene is present cannot be fused with other polyurethane foam particles, thus naturally leaving a breathable channel.

[0020] 2. The present application utilizes the hydrophilic hydroxyl groups of graphene oxide to react with the hydroxyl groups or isocyanate groups on the polyurethane to form a stable link. At the same time, the hydrophobic structure on the other side prevents the polyurethane foam particles from merging in some areas, thus leaving a naturally formed air permeable channel on the formed midsole, which is mainly formed by graphene. Since the amount of graphene oxide added is very small, it does not affect the bonding strength between the foamed particles. At the same time, some of the air permeable channels left can well increase the air permeability of the midsole. Due to the presence of graphene, its strong adsorption performance makes the midsole have a good deodorizing effect.

[0021] 3. The present application also provides a midsole with an integrated visual effect. In the method for manufacturing the midsole, a mold with dense air holes is used. The dense air holes make it easy to obtain a surface that is more consistent with the surface of the mold. During the high-temperature treatment process, the surface density increases, and the wear resistance of the visual part is improved. The popcorn pattern disappears, and it has an integrated effect, so that more complex and delicate patterns can be set on its side without being affected by the popcorn pattern. The method still retains the excellent elasticity of the popcorn midsole. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 Schematic diagram of increased gas permeability resulting from the use of graphene oxide.

[0023] Figure 2 Here is a photo of the sparse holes in the mold at the non-integrated visual effect.

[0024] Figure 3 This is a photo of the mold's dense holes at the integrated visual effect area. DETAILED DESCRIPTION

[0025] The specific embodiments of the present invention will be described below with reference to the accompanying drawings.

[0026] Example embodiments will now be described more fully with reference to the accompanying drawings. However, example embodiments can be implemented in many forms and should not be construed as limited to the embodiments set forth herein; rather, these embodiments are provided so that the present invention will be comprehensive and complete and fully convey the concepts of the example embodiments to those skilled in the art. The same reference numerals in the figures represent the same or similar parts, and thus their repeated description will be omitted.

[0027] In addition, the described features, structures or characteristics may be combined in one or more embodiments in any suitable manner. In the following description, many specific details are provided to provide a full understanding of the embodiments of the present invention. However, those skilled in the art will appreciate that the technical solution of the present invention can be practiced without one or more of the specific details, or other methods, components, devices, steps, etc. may be adopted. In other cases, known methods, devices, implementations or operations are not shown or described in detail to avoid blurring various aspects of the present invention.

[0028] Graphene oxide is an oxide of graphene, generally represented by GO, and its color is brownish yellow. Common products on the market are powder, flake and solution. After oxidation, the number of oxygen-containing functional groups increases, making its properties more active than graphene, and its properties can be improved through various reactions with oxygen-containing functional groups. The above-mentioned graphene oxide in this application refers to a flaky graphene having 5 to 30 layers of single-layer graphene (i.e., a thickness of about 1.5 nanometers to 15 nanometers), and the single-layer graphene is connected to a group that can combine with a hydroxyl group or an isocyanate group. The preferred graphene oxide in this application is sulfonated graphene. WO2015184843A1 discloses a method for preparing sulfonated graphene from organic materials and sulfonated graphene. The graphene prepared by the method may have the following structural characteristics: the sulfonated graphene wherein the sheet diameter of the sulfonated graphene (the plane diameter of the material) is greater than or equal to 100 microns and less than 1000 microns; the thickness of each of the sulfonated graphenes is 5 to 10 nanometers; and the thickness (the distance in the normal direction of the material plane) of the sulfonated graphene, the sheet diameter uniformity and the thickness uniformity are both greater than 90%; the sheet diameter uniformity and the thickness uniformity of the sulfonated graphene are both greater than 90%.

[0029] The first aspect of the present application provides a method for preparing a midsole using polyurethane foam particles and the midsole prepared therefrom. The method comprises: fusing the polyurethane foam particles having graphene oxide on the surface with each other in a midsole mold under steam heating conditions to form the midsole.

[0030] During the high-temperature fusion process of graphene oxide on the surface of polyurethane foam particles, the graphene oxide itself forms a stable chemical bond with the hydroxyl or isocyanate groups on the surface of polyurethane foam particles. The graphene has a multi-layer structure so that the polyurethane foam particles where there is graphene cannot be fused with other polyurethane foam particles, thus naturally leaving a breathable channel. The breathable channel is made into the midsole of the shoe, and the wearer can fully release the breathability of the midsole by wearing it for about 30,000 steps (different people will have slightly different steps).

[0031] In the present application, the hydrophilic hydroxyl groups of graphene oxide can react with the hydroxyl groups or isocyanate groups on polyurethane to form a stable link, while the hydrophobic structure on the other side prevents the polyurethane foam particles from merging in some areas, thus leaving a naturally formed breathable channel on the formed midsole. The channel is mainly formed by graphene.

[0032] In addition, due to the presence of graphene, its strong adsorption performance makes the midsole have a good deodorizing effect. In this application, the evaluation of the midsole's air permeability and deodorizing effect is completed in the same experiment. In fact, the air permeability and deodorizing effects are often difficult for the wearer to distinguish. After the shoes are worn, the odor left behind becomes less. Whether it is caused by adsorption or gas flow, it is not necessary for the wearer to distinguish. Therefore, in this application, the deodorizing ability and air permeability of the midsole are evaluated mainly by evaluating the deodorizing property.

[0033] In some embodiments, in the above method for preparing a midsole using polyurethane foam particles, the amount of the graphene oxide is 0.02wt% to 2wt% of the polyurethane foam particles. Within this range, the added amount can be 0.06wt% to 1wt%, such as 0.07wt% to 0.2wt%, such as 0.08wt% to 0.4wt%, such as 0.09wt% to 0.3wt%, such as 0.1wt% to 0.2wt%.

[0034] Since the amount of graphene oxide added is very small, it does not affect the bonding strength between the foamed particles. At the same time, some breathable channels left behind can greatly increase the breathability of the midsole.

[0035] In some embodiments, in the above method for preparing a midsole using polyurethane foam particles, the polyurethane foam particles having graphene oxide on the surface are prepared as follows: a suspension of graphene oxide is contacted with the polyurethane foam particles to obtain polyurethane foam particles having graphene oxide on the surface. In these embodiments, the graphene oxide is physically combined with the polyurethane foam particles in the form of a suspension, and a strong chemical bond is formed during the secondary foaming process.

[0036] In some embodiments, in the above-mentioned method for preparing a midsole using polyurethane foam particles, the polyurethane foam particles having graphene oxide on the surface are prepared as follows: a molten polyurethane matrix is ​​fully mixed with a supercritical foaming agent (such as carbon dioxide or nitrogen or other gases) to form a single-phase mixed sol; The single-phase mixed sol is passed through an extrusion die and enters a normal pressure state, so that a large number of bubble nuclei are precipitated from the foaming agent and expand to obtain hot polyurethane foam particles. The powdered graphene oxide is mixed with the hot polyurethane foam particles and cooled to form the polyurethane foam particles having graphene oxide on the surface.

[0037] In these embodiments, the graphene oxide is combined with hot polyurethane foam particles in the form of solid powder, which is easy to adhere to, and the obtained polyurethane foam particles with graphene oxide on the surface can be directly used to form the midsole.

[0038] In some embodiments, in the above method for preparing a midsole using polyurethane foam particles, the above graphene oxide suspension further contains a binder. The added binder is used to increase the adhesion between the polyurethane foam particles to compensate for the reduced adhesion between the foam particles that may be caused by the graphene oxide.

[0039] In some embodiments, the above-mentioned method of preparing a midsole using polyurethane foam particles, wherein the above-mentioned graphene oxide is sulfonated graphene, and the sheet diameter of the above-mentioned sulfonated graphene (the plane diameter of the material) is greater than or equal to 100 microns and less than 1000 microns; the thickness of each of the above-mentioned sulfonated graphene is 5 to 10 nanometers; and the thickness (the distance in the normal direction of the material plane) of the above-mentioned sulfonated graphene The uniformity of the sheet diameter and the uniformity of the thickness are both greater than 90%; the sheet diameter uniformity and the thickness uniformity of the above-mentioned sulfonated graphene are both greater than 90%.

[0040] The sulfonated graphene specifically used in the present application is a type of graphene oxide, and the oxidation of graphene is achieved by sulfonation, and is prepared according to the specific method in Example 4 disclosed in WO2015184843A1.

[0041] The method of the present application can also be used to prepare a midsole with an integrally formed visual effect. Usually, a popcorn sole does not have an integrally formed visual effect. On the contrary, the presence of a popcorn visual effect can be clearly seen from the side of the midsole of the shoe. In some embodiments, the above-mentioned method of preparing a midsole using polyurethane foam particles, wherein the above-mentioned midsole is a midsole with an integrally formed visual effect, and at least part of the area of ​​the above-mentioned midsole with an integrally formed visual effect has an integrally formed visual effect, that is, there is no popcorn-like pattern in this area, which is called an integrally formed visual area, and is characterized in that the above-mentioned mold is a porous mold, and a plurality of first air holes are provided in the visual part corresponding to the above-mentioned integrally formed visual area, wherein the area of ​​each of the above-mentioned first air holes is 0.01 square millimeters to 0.25 square millimeters, and the number of the above-mentioned first air holes is greater than 50 / square centimeter.

[0042] The above methods include: The first step is to place the foamed particles in the mold, and introduce steam at a first temperature into the mold to allow the foamed particles to undergo secondary foaming and fuse with each other to form a midsole precursor; The second step is to maintain one or more of the above molds in an atmosphere of a second temperature, wherein the second temperature is higher than the first temperature, so that an integrated molding visual effect is formed in the integrated molding visual area of ​​the above midsole precursor to form the above midsole.

[0043] This embodiment has a special technical effect. The dense air pores can easily obtain a surface that is more consistent with the surface of the mold. During the high-temperature treatment process, the surface density increases and the wear resistance of the visual part is improved. The popcorn pattern disappears, and it has an one-piece molding effect, so that more complex and delicate patterns can be set on its side without being affected by the popcorn pattern.

[0044] In some embodiments, the above-mentioned method of preparing a midsole using polyurethane foam particles, wherein the above-mentioned one-piece molding visual effect includes: the above-mentioned one-piece molding visual area does not contain a popcorn-like pattern, and the above-mentioned one-piece molding visual area includes a fine pattern, and the above-mentioned fine pattern is a pattern feature with a size of 0.2mm to 2.0mm, and the size of the above-mentioned pattern feature refers to the minimum size of the above-mentioned pattern feature.

[0045] In some embodiments, the above-mentioned method of preparing a midsole using polyurethane foam particles, wherein the above-mentioned foam particles are made of at least one material selected from the following: polyester polyurethane, polyether polyurethane, aliphatic polyurethane. It should be particularly pointed out that the method of the present application is actually also applicable to other similar foam particles, such as foam particles made of the following substances: modified nylon elastomer Pebax, polyester elastomer TPEE, ethylene-vinyl acetate copolymer EVA.

[0046] In some embodiments, in the above-mentioned method of preparing a midsole using polyurethane foam particles, the above-mentioned integrally formed visual effect area includes the side of the midsole.

[0047] In some embodiments, in the above-mentioned method of preparing a midsole using polyurethane foam particles, a non-visual portion of the above-mentioned mold that does not correspond to the above-mentioned one-piece molded visual area is provided with a plurality of second air holes, an area of ​​each of the above-mentioned second air holes is greater than 0.3 square millimeters and less than 3 square millimeters, and the number of the above-mentioned second air holes is less than 10 / square centimeter, for example, 0.5 to 3 / square centimeter.

[0048] In non-visual areas, the mold uses large ventilation holes with a small distribution number, so that the midsole retains the appearance of popcorn and retains some roughness. This shape is more suitable for bonding with other materials.

[0049] In some embodiments, in the above method of preparing a midsole using polyurethane foam particles, the surface of the above visual part of the above mold has a smaller roughness than the surface of the above non-visual part, that is, the non-visual part is rougher. In this embodiment, the rough edge is easier to bond with other shoe materials such as the outsole. The visual part is not rough and can show a better visual effect.

[0050] In some embodiments, in the above method of preparing a midsole using polyurethane foam particles, the surface of the visual part of the mold is provided with a fine pattern.

[0051] In some embodiments, in the above-mentioned method of preparing a midsole using polyurethane foam particles, the first temperature is between the softening point of the foam particles and a temperature 18°C ​​higher than the softening point, the treatment time is 1 minute to 20 minutes, and the second temperature is a temperature 20°C to 30°C higher than the first temperature, and the treatment time is 1 minute to 20 minutes.

[0052] In some embodiments, the polyurethane is an aliphatic polyurethane, and the aliphatic polyurethane is prepared by reacting a liquid composition, and the liquid composition comprises: The invention comprises a polyurethane generating component and a reaction catalyst, wherein the polyurethane generating component comprises an isocyanate component A and an isocyanate reactive component B, and the isocyanate component A comprises one or more selected from the following: an aliphatic diisocyanate and an aliphatic polyisocyanate; The isocyanate-reactive component B comprises: B1) one or more organic polyols with a functionality of 2 to 3; B2) low molecular weight polyvinyl alcohol, wherein the molecular weight of the low molecular weight polyvinyl alcohol is 300 to 10000, wherein the initial viscosity of the liquid composition at 25°C is 50-5000 mPa.s (measured according to DIN EN 53019), and the ratio of the number of NCO groups in the isocyanate component A to the number of OH groups in the isocyanate-reactive component B is 1.05:1 – 1.1:1.

[0053] The aliphatic polyurethane polymer prepared in this embodiment is particularly suitable for preparing the midsole mentioned above in this application. The polyurethane prepared by the composition disclosed by this method has a hydrocarbon skeleton of polyvinyl alcohol and has good biocompatibility. The polyurethane foam material has at least one of the effects of temperature resistance, good thermoplasticity, and stable mold shrinkage, and can achieve stable and controllable shaping of the polyurethane foam material under high temperature conditions.

[0054] The reaction catalyst is a latent catalyst, which catalyzes at a temperature of 60° C. to 100° C. The weight content of the reaction catalyst is 0.01 to 6 parts by weight, calculated based on 100 parts by weight of the polyurethane generating components.

[0055] There is no limitation on the type of catalyst used in the present application, as long as it is suitable for the chemical reaction in the present application. In some embodiments, the reaction catalyst can be one or more of aromatic amines, imidazoles, acid anhydrides, dicyandiamides, organic hydrazide compounds, such as cyanoguanidine, 4,4'-diaminodiphenyl sulfone, N-acyl imidazole compounds, and cyanoacetyl compounds. For example, Aradur 3380 purchased from Huntsman Advanced Chemical Materials Co., Ltd. is an acid anhydride curing agent used in the embodiments of the present application.

[0056] The liquid composition may further include at least one auxiliary agent selected from the group consisting of a defoamer, a release agent, a leveling agent, a durability aid, a flow aid, an organic color powder, an inorganic color powder, and a color paste.

[0057] The present application also provides a midsole prepared by any of the methods described above in the present application.

[0058] In some embodiments, the above-mentioned midsole of the present application is a midsole with an integrated molding visual effect, wherein the above-mentioned midsole with an integrated molding visual effect is made by subjecting foamed particles to secondary foaming molding in a mold, and at least a partial area has an integrated molding visual effect, that is, there is no popcorn-like pattern visually in this area, which is called an integrated molding visual area.

[0059] In some embodiments, in the midsole described above in the present application, the one-piece formed visual area includes a side surface of the midsole.

[0060] In some embodiments, in the midsole of the present application, the above-mentioned integrally formed visual area also includes an area with a pattern similar to popcorn visually, which is called a non-integrated visual area, wherein the surface density of the above-mentioned integrally formed visual area is 1.1 times or more of the surface density of the above-mentioned non-integrated visual area, and the surface density of the above-mentioned integrally formed visual area is 1.3 times or more of the density of the inner area of ​​the midsole. In a specific embodiment, in the non-integrated visual area: the surface density is 0.17 g / cm 3 Left and right, 0.15g / cm in the middle 3 ; In the integrated visual area: skin density 0.195g / cm 3 Left and right, 0.15g / cm in the middle 3 .

[0061] In some embodiments, in the midsole described above, the foamed particles are made of at least one material selected from the following: polyester polyurethane, polyether polyurethane, aliphatic polyurethane. It should be further explained that the foamed particles described above can be made of the following materials: modified nylon elastomer Pebax, polyester elastomer TPEE, ethylene-vinyl acetate copolymer EVA.

[0062] In some embodiments, in the midsole described above in the present application, the foamed particles include: 80wt% to 100wt% of foamed particles made of polyurethane, wherein the polyurethane is selected from at least one of the following: polyester polyurethane, polyether polyurethane, aliphatic polyurethane, or a combination thereof; and 1wt% to 20wt% of foamed particles made of the following substances: polyether nylon elastomer (pebax), polyester elastomer (TPEE), ethylene vinyl acetate polymer (EVA).

[0063] In some embodiments, in the midsole described above in the present application, the foamed particles include: 82wt% to 98wt% of foamed particles made of polyurethane, wherein the polyurethane is selected from at least one of the following: polyester polyurethane, polyether polyurethane, aliphatic polyurethane, or a combination thereof; and 2wt% to 12wt% of foamed particles made of the following substances: polyether nylon elastomer (pebax), polyester elastomer (TPEE), ethylene vinyl acetate polymer (EVA).

[0064] The present application also provides a shoe, which comprises the midsole according to the present application.

[0065] Table 2 Raw materials and sources

[0066] Example 1 [Method for preparing aliphatic polyurethane] The polyurethane is an aliphatic polyurethane, which is prepared by reacting a liquid composition. The liquid composition comprises: The invention comprises a polyurethane generating component and a reaction catalyst, wherein the polyurethane generating component comprises an isocyanate component A and an isocyanate reactive component B, and the isocyanate component A comprises one or more selected from the following: an aliphatic diisocyanate and an aliphatic polyisocyanate; The isocyanate-reactive component B comprises: B1) one or more organic polyols with a functionality of 2 to 3; B2) low molecular weight polyvinyl alcohol, wherein the molecular weight of the low molecular weight polyvinyl alcohol is 300 to 10000, wherein the initial viscosity of the liquid composition at 25°C is 50-5000 mPa.s (measured according to DIN EN 53019), and the ratio of the number of NCO groups in the isocyanate component A to the number of OH groups in the isocyanate-reactive component B is 1.05:1 – 1.1:1.

[0067] The reaction catalyst is a latent catalyst, which catalyzes at a temperature of 60° C. to 100° C. The weight content of the reaction catalyst is 0.01 to 6 parts by weight, calculated based on 100 parts by weight of the polyurethane generating components.

[0068] There is no limitation on the type of catalyst used in the present application, as long as it is suitable for the chemical reaction in the present application. In some embodiments, the reaction catalyst can be one or more of aromatic amines, imidazoles, acid anhydrides, dicyandiamides, organic hydrazide compounds, such as cyanoguanidine, 4,4'-diaminodiphenyl sulfone, N-acyl imidazole compounds, and cyanoacetyl compounds. For example, Aradur 3380 purchased from Huntsman Advanced Chemical Materials Co., Ltd. is an acid anhydride curing agent used in the embodiments of the present application.

[0069] The aliphatic polyurethane polymer prepared in this embodiment is particularly suitable for preparing the midsole mentioned above in this application. The polyurethane prepared by the composition disclosed by this method has a hydrocarbon skeleton of polyvinyl alcohol and has good biocompatibility. The polyurethane foam material has at least one of the effects of temperature resistance, good thermoplasticity, and stable mold shrinkage, and can achieve stable and controllable shaping of the polyurethane foam material under high temperature conditions. The obtained aliphatic polyurethane is in granular form.

[0070] Example 2 [Preparation of foamed particles by one-step foaming of supercritical fluid] The granular aliphatic polyurethane obtained in Example 1 was used to prepare foamed particles by a supercritical fluid foaming method.

[0071] The polyurethane matrix in a molten state is fully mixed with a foaming agent in a supercritical state (such as carbon dioxide or nitrogen or other gases) to form a single-phase mixed sol; The above-mentioned single-phase mixed sol is passed through an extrusion die and enters a normal pressure state, so that a large number of bubble nuclei are precipitated from the foaming agent and expand to obtain hot polyurethane foam particles.

[0072] Example 3 [Combining graphene oxide powder on the basis of Example 2] The powdered graphene oxide is mixed with the hot polyurethane foam particles and cooled to form the polyurethane foam particles having graphene oxide on the surface.

[0073] The above-mentioned graphene oxide is sulfonated graphene, and the above-mentioned sulfonated graphene has a sheet diameter (the plane diameter of the material) greater than or equal to 100 microns to less than 1000 microns; the thickness of each of the above-mentioned sulfonated graphene is 5 to 10 nanometers; and the thickness (the distance in the normal direction of the material plane) and the sheet diameter uniformity of the above-mentioned sulfonated graphene are both greater than 90%; the sheet diameter uniformity and the thickness uniformity of the above-mentioned sulfonated graphene are both greater than 90%.

[0074] The amount of graphene oxide applied is 0.2 wt % based on the weight of the polyurethane particles, and the first polyurethane foam particles with graphene oxide on the surface are obtained. The graphene oxide is combined with the hot polyurethane foam particles in the form of solid powder and is easy to adhere.

[0075] Example 4 [Using graphene oxide suspension to set graphene oxide on foamed particles] The hot polyurethane foam particles obtained in Example 2 are cooled to obtain polyurethane foam particles. Graphene oxide is prepared together with a surfactant and water to form a graphene oxide suspension. The graphene oxide suspension is contacted with the polyurethane foam particles to obtain a second type of polyurethane foam particles having graphene oxide on the surface.

[0076] Graphene oxide is physically combined with polyurethane foam particles in the form of a suspension, and a strong chemical bond is formed during the secondary foaming process.

[0077] Example 5 [Secondary foaming of water vapor to prepare midsole] The (first or second) polyurethane foam particles having graphene oxide on the surface are fused with each other in a midsole mold under the condition of being heated by water vapor to form the above-mentioned midsole.

[0078] The above-mentioned midsole is a midsole with an integrally molded visual effect, and at least part of the area of ​​the above-mentioned midsole with an integrally molded visual effect has an integrally molded visual effect, that is, there is no popcorn-like pattern in this area, which is called the integrally molded visual area. The above-mentioned mold is a porous mold, and a plurality of first air holes are arranged in the visual part corresponding to the above-mentioned integrally molded visual area, wherein the area of ​​each of the above-mentioned first air holes is 0.01 square millimeters to 0.25 square millimeters, and the number of the above-mentioned first air holes is greater than 50 per square centimeter.

[0079] The above methods include: The first step is to place the foamed particles in the mold, and introduce steam at a first temperature into the mold to allow the foamed particles to undergo secondary foaming and fuse with each other to form a midsole precursor; In the second step, one or more of the above-mentioned molds are maintained in an atmosphere of a second temperature, wherein the above-mentioned second temperature is higher than the above-mentioned first temperature, so that an integrated molding visual effect is formed in the integrated molding visual area of ​​the above-mentioned midsole precursor to form the above-mentioned midsole 5-1 and midsole 5-2, wherein the above-mentioned midsole 5-1 is prepared by using the first kind of polyurethane foam particles having graphene oxide on the surface obtained in Example 3, and the above-mentioned midsole 5-2 is prepared by using the second kind of polyurethane foam particles having graphene oxide on the surface obtained in Example 4.

[0080] The first temperature is between the softening point of the foamed particles and a temperature 18°C ​​higher than the softening point, and the treatment time is 3 minutes; The second temperature is 20° C. to 30° C. higher than the first temperature, and the treatment time is 3 minutes.

[0081] During the high-temperature fusion process of graphene oxide on the surface of polyurethane foam particles, the graphene oxide itself also forms a stable chemical bond with the hydroxyl or isocyanate groups on the surface of the polyurethane foam particles. The graphene has a multi-layer structure, so the polyurethane foam particles where there is graphene cannot be fused with other polyurethane foam particles, thus naturally leaving a breathable channel.

[0082] In the present application, the hydrophilic hydroxyl groups of graphene oxide can react with the hydroxyl groups or isocyanate groups on polyurethane to form a stable link, while the hydrophobic structure on the other side prevents the polyurethane foam particles from merging in some areas, thus leaving a naturally formed breathable channel on the formed midsole. The channel is mainly formed by graphene.

[0083] Since the amount of graphene oxide added is very small, it does not affect the bonding strength between the foamed particles. At the same time, some breathable channels left behind can greatly increase the breathability of the midsole.

[0084] Technical effect: Dense air holes can easily obtain a surface that is more consistent with the surface of the mold. During the high-temperature treatment process, the surface density increases and the wear resistance of the visual part is improved. The popcorn pattern disappears, and it has an one-piece molding effect, so that more complex and delicate patterns can be set on its side without being affected by the popcorn pattern.

[0085] The foamed particles with an average diameter of 2 mm made of polyester polyurethane are placed in a 20x20x4cm mold. The mold is a porous mold, the area of ​​the air holes is 0.01 square millimeters, and the number of the first air holes is 100 per square centimeter. The mold is provided with a plurality of second air holes in the non-visual part not corresponding to the one-piece visual area. The area of ​​each second air hole is 0.8 square millimeters, and the number of the second air holes is 3 per square centimeter.

[0086] The non-visual part is coarser than the visual part.

[0087] Steam at 150°C is introduced into the mold to cause the foamed particles to undergo secondary foaming and fuse together to form an integral foaming template. The mold is maintained in an atmosphere of 170°C for high-temperature treatment, and then water-cooled and molded again, so that the integral foaming template has an integrated visual effect area that visually does not have a popcorn-like pattern.

[0088] Embodiment 6 [Shoemaking] The midsole 5-1 and the midsole 5-2 in Example 5 are made into shoes 5-1 and shoes 5-2 respectively.

[0089] The specific method is to bond the midsole to the rubber outsole, combine it with the upper, and set the insole.

[0090] Example 7 [Using the particles obtained in Example 2, without adding graphene oxide, to directly prepare shoes] The hot polyurethane foam particles obtained in Example 2 were cooled to obtain polyurethane foam particles. The midsole was prepared by the method of Example 5, and the shoe 5-3 was prepared by the method of Example 6. Example

[0091] The method of Example 5 was adopted to prepare the midsole, and the method of Example 6 was adopted to make the shoes, except that commercially available foamed particles (polyester polyurethane-A1, polyether polyurethane-A2, aliphatic polyurethane-A3, modified nylon elastomer Pebax-A4, polyester elastomer TPEE-A5, ethylene-vinyl acetate copolymer EVA-A6) were used to obtain shoes A1, shoes A2, shoes A3, shoes A4, shoes A5, and shoes A6. Example

[0092] The method of Example 4 is adopted to make the surface of the foamed particles have graphene oxide, except that commercially available foamed particles (polyester polyurethane-B1, polyether polyurethane-B2, aliphatic polyurethane-B3, modified nylon elastomer Pebax-B4, polyester elastomer TPEE-B5, ethylene-vinyl acetate copolymer EVA-B6) are used to prepare the foamed particles with graphene oxide on the surface.

[0093] The method of Example 5 was used to prepare the midsole, and the method of Example 6 was used to make the shoes, to obtain shoes B1, shoes B2, shoes B3, shoes B4, shoes B5, and shoes B6. Example

[0094] The method of Example 5 is used to make the surface of the foamed particles have graphene oxide, except that 12wt% of modified nylon elastomer Pebax-5-4, polyester elastomer TPEE-5-5, ethylene-vinyl acetate copolymer EVA-5-6) is added to the foamed particles to prepare foamed particles with graphene oxide on the surface.

[0095] The midsole was prepared by the method of Example 5, and the shoe was made by the method of Example 6 to obtain shoe 5-4, shoe 5-5, and shoe 5-6.

[0096] Comparative Example 11 The method of Example 5 is adopted to prepare the midsole, and the method of Example 6 is adopted to make the shoe, except that the following foamed particles are used (foamed particles-5-7 of Example 2, polyester polyurethane-C1, polyether polyurethane-C2, aliphatic polyurethane-C3, modified nylon elastomer Pebax-C4, polyester elastomer TPEE-C5, ethylene-vinyl acetate copolymer EVA-C6), and the second step is not performed, that is, the step of "maintaining one or more of the above-mentioned molds in an atmosphere of the second temperature" is not performed, and the obtained midsole precursor is directly used to make shoes to obtain shoes 5-7, shoes C1, shoes C2, shoes C3, shoes C4, shoes C5, and shoes C6.

[0097] Test [Change shoes 5-1 to 5-7, A1-A6, B1-B6, C1-C6] Before testing, step on the shoes for about 30,000 steps to thoroughly activate the graphene oxide breathable channels.

[0098] Two parallel experiments were performed for each test; Test 1 [Left foot comparison example 11, right foot implementation example] Exercise for one day, about 30,000 steps.

[0099] Test 2 [right foot comparison example 11, left foot implementation example] Exercise for one day, about 30,000 steps.

[0100] The shoes prepared in each embodiment were compared with the shoes prepared with the same midsole material in Comparative Example 11, and the odor of the two shoes was evaluated. The results were averaged from the two tests. If the results were too different, the test was repeated. That is, shoes 5-1 to 5-6 were compared with shoes 5-7 in Comparative Example 11 as a group, and all the test values ​​of shoes 5-7 were averaged. Shoes A1 and B1 were compared with C1 in Comparative Example 11 as a group, and all the test values ​​of shoe C1 were averaged. Shoes A2 and B2 were compared with C2 in Comparative Example 11 as a group, and all the test values ​​of shoe C2 were averaged, and so on.

[0101] The odor is divided into 11 levels from 0 to 10. Among them, when the odor level is 0, the odor is the least, and when the odor level is 10, the odor is the strongest.

[0102] The tear strength of Example 5-4 is used as a benchmark for comparison. The increase in surface density and tear strength refers to the increase in the values ​​of the integrated visual effect area of ​​the shoe relative to the values ​​of the non-integrated visual effect area. Specifically, if the surface density of the non-integrated visual area is 0.17 g / cm 3 The skin density in the integrated visual area is 0.195g / cm 3 , the increase in epidermis density is 14.7%. It should be noted that the surface density of the one-piece visual effect area is 1.3 times or higher than the density of the inner area of ​​the midsole. The specific measurement values ​​are not given separately in the table. The tear strength of the sole is tested using the ASTMD-624 standard. First, a sheet containing a 2mm thick epidermis is cut from the area to be tested, and then it is punched out with a punch, and the tear strength is tested using a tensile testing machine (in kg / cm). It should be noted that the tear strength of the one-piece visual effect area is important because, under normal circumstances, the one-piece visual effect area is susceptible to external shear forces during movement.

[0103] Heat resistance is measured by measuring the Vicat softening point temperature. Resilience refers to the ability of the sole to bounce back the impacted object after being deformed by impact, and is measured according to DB35∕T 1937-2020.

[0104] In Table 1, the mass / weight proportions of thermoplastic polyurethane and other materials are 85% and 15% respectively.

[0105] Table 1. Test results

[0106] The above is only a specific implementation of the present invention, but the design concept of the present invention is not limited thereto. Any non-substantial changes to the present invention using this concept shall be deemed as an infringement of the protection scope of the present invention.

Claims

1. A method for preparing a midsole using polyurethane foam particles, characterized in that: The steps include: 1) Preparation of foamed particles having graphene oxide on the surface, as follows: Method S1, contacting a graphene oxide suspension with the polyurethane foam particles, wherein the graphene oxide suspension also contains a binder, to obtain polyurethane foam particles having graphene oxide on the surface; Alternatively, method S2, fully mixing the polyurethane matrix in a molten state with the foaming agent in a supercritical state to form a single-phase mixed sol; The single-phase mixed sol is passed through an extrusion die to enter a normal pressure state, so that a large number of bubble nuclei are precipitated from the foaming agent and expand to obtain hot polyurethane foam particles; Mixing powdered graphene oxide with the hot polyurethane foam particles, and cooling the mixture to form the polyurethane foam particles having graphene oxide on the surface; 2) placing the foamed particles in a mold, and introducing steam at a first temperature into the mold, wherein the first temperature is between the softening point of the foamed particles and a temperature 18° C. higher than the softening point, and the treatment time is 1 minute to 20 minutes, so that the foamed particles undergo secondary foaming and are mutually welded to form a midsole precursor; 3) maintaining one or more molds in an atmosphere of a second temperature, wherein the second temperature is 20° C. to 30° C. higher than the first temperature, for a treatment time of 1 minute to 20 minutes, so that an integrated molding visual effect is formed in the integrated molding visual area of ​​the midsole precursor to form the midsole.

2. A method for preparing a midsole using polyurethane foam particles as claimed in claim 1, characterized in that: The amount of the graphene oxide is 0.02wt%-2wt% of the polyurethane foam particles.

3. The method for preparing a midsole using polyurethane foam particles according to claim 1, characterized in that: The graphene oxide is sulfonated graphene, the flake diameter of the sulfonated graphene is 100 micrometers to 1000 micrometers, the thickness of each sulfonated graphene is 5nm to 10nm, and the flake diameter uniformity and thickness uniformity of the sulfonated graphene are both greater than 90%.

4. The method for preparing a midsole using polyurethane foam particles according to claim 1, characterized in that: The mold is a porous mold, which is provided with a plurality of first air holes corresponding to the visual part of the integrally formed visual area, wherein the area of ​​each of the first air holes is 0.01 square millimeters to 0.25 square millimeters, and the number of the first air holes is greater than 50 per square centimeter.

5. The method for preparing a midsole using polyurethane foam particles according to claim 1, characterized in that: The foamed particles include 60wt% to 98wt% of foamed particles made of polyurethane and 2wt% to 40wt% of foamed particles made of other materials, wherein the polyurethane is one or more of polyester polyurethane, polyether polyurethane and aliphatic polyurethane, and the other materials are one or more of polyether nylon elastomer (PEBAX), polyester elastomer (TPEE) and ethylene vinyl acetate polymer (EVA).

6. The method for preparing a midsole using polyurethane foam particles according to claim 1, characterized in that: A non-visual portion of the mold that does not correspond to the one-piece visual area is provided with a plurality of second air holes, an area of ​​each of the second air holes is greater than 0.3 square millimeters and less than 3 square millimeters, and the number of the second air holes is less than 10 per square centimeter.

7. A method for preparing a midsole using polyurethane foam particles as claimed in claim 5, characterized in that: The polyurethane is an aliphatic polyurethane, which is prepared by reacting a liquid composition, wherein the liquid composition comprises a polyurethane generating component and a reaction catalyst, wherein the polyurethane generating component comprises an isocyanate component A and an isocyanate reactive component B, and the isocyanate component A comprises an aliphatic diisocyanate and / or an aliphatic polyisocyanate; The isocyanate-reactive component B comprises: B1) one or more organic polyols with a functionality of 2-3; B2) low molecular weight polyvinyl alcohol, wherein the molecular weight of the low molecular weight polyvinyl alcohol is 300 to 10,000, wherein the initial viscosity of the liquid composition at 25° C. is 50-5,000 mPa.s (measured according to DIN EN 53019), and the ratio of the number of NCO groups in the isocyanate component A to the number of OH groups in the isocyanate component B is 1.05:1 – 1.1:

1.

8. A midsole, characterized in that: It comprises a midsole made by the method for making a midsole using polyurethane foam particles according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Method for preparing sulfonated graphene from organic material and sulfonated graphene

    WO2015184843A1